Solar UV-B and ABA Are Involved in Phenol Metabolism of Vitis vinifera L. Increasing Biosynthesis of Berry Skin Polyphenols - Berli, Federico Javier (2011)
It has been previously found that abscisic acid (ABA) participates in the activation of grapevine leaf tissue defense against potentially damaging effects of solar ultraviolet-B radiation (UV-B), apparently by triggering biosynthesis of phenols that filter the harmful radiation and act as antioxidants. The present work studies the effect of solar UV-B and exogenously applied ABA on berry growth, sugar accumulation, and phenol (anthocyanin and nonanthocyanin) profiles across berry development and ripening of Vitis vinifera L. cv. Malbec in a vineyard at 1450 m of altitude. The grapevines were exposed to relatively high UV-B irradiation (normal sunlight;+UV-B) and also to a reduced UV-B treatment (filter exclusion; -UV-B). These two UV-B treatments were combined with weekly spray applications to the leaves and berries of 1 mM ABA (+ABA) or H2O (-ABA). Reduction of UV-B delayed berry development and maturation, whereas the +UV-B and +ABA combined treatment hastened berry sugar and phenol accumulation. +UV-B/+ABA treatments also reduced berry growth and decreased sugar per berry without affecting sugar concentration (°Brix) at harvest. Berry skin ABA levels were higher in the +UV-B and +ABA combined treatment, which also hastened the onset of ripening up to 20 days. Berry skin ABA levels then decreased toward harvest, implying a possible role for ABA in the control of ripening in this nonclimacteric fruit. Under both +UV-B and +ABA treatments berry skin phenols were additively increased with a change in anthocyanin and nonanthocyanin profiles and increases in the proportion of phenols with high antioxidant capacity.